2022
DOI: 10.1039/d1cc06816d
|View full text |Cite
|
Sign up to set email alerts
|

Substitution at sp3 boron of a six-membered NHC·BH3: convenient access to a dihydroxyborenium cation

Abstract: Herein, we have undertaken the synthesis and reactivity of a 6-membered saturated NHC borane aduct (1). Direct electrophilic halogenation of 1 with a stoichiometric amount of I2 led to NHC...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 34 publications
6
40
0
Order By: Relevance
“…Following the isolation of 6-SIDipp·BH 3 , 20 we were curious to study the reactions of 6-SIDipp with other boranes. The reaction of 6-SIDipp with one equivalent of BHCl 2 forms Lewis acid–base adducts ( 3 ) (Scheme 2), which show resonances at −7.4 ppm in the 11 B NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the isolation of 6-SIDipp·BH 3 , 20 we were curious to study the reactions of 6-SIDipp with other boranes. The reaction of 6-SIDipp with one equivalent of BHCl 2 forms Lewis acid–base adducts ( 3 ) (Scheme 2), which show resonances at −7.4 ppm in the 11 B NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous communication, we have shown that the reaction of a saturated six-membered N-heterocyclic carbene (6-SIDipp) with BH 3 led to the formation of an adduct, 6-SIDipp·BH 3 . 20 The latter undergoes a facile electrophilic substitution reaction with I 2 , leading to 6-SIDipp mono- and diboryl iodides, selectively. 20 However, the corresponding reaction with Br 2 was not selective, and resulted in a mixture of mono-, di-, and tribromide adducts, akin to what was noted by Curran and coworkers with 1,3-bis-(2,6-diisopropylphenyl)imidazole-2-ylidine (5-IDipp).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of one and two chlorine atoms from the tetra coordinated boron atom of 2 resulted in the formation of 5-SIDipp•BPhCl(OTf), 5a, and 5-SIDipp-BPh(ONO 2 ) 2 , 6 (Scheme 3). The functional groups such as nitrate and triflate are rarely found to bind with the boron atom [5,9,[20][21][22][23][24][25][26]. 5a crystallizes in the monoclinic P2 1 /n space group (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous works, we have shown the nucleophilic substitution at 5-SIDipp•MeBCl 2 (5-SIDipp = 1,3,-bis-(2,6diisopropylphenyl)imidazolin-2-ylidine) [8]. Further, we have explored the substitution at 6-SIDipp•BH 3 (6-SIDpp = 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene) center and the introduction of rare functional groups such as -OTf, -NO 3 [9]. Although the saturated NHCs are more nucleophilic than its unsaturated analogue, the earlier work on the synthesis of more than two dozen of NHC•borane and haloborane complexes relied on the unsaturated five-membered NHC [1][2][3][4][5][6][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%